2019
DOI: 10.1038/s41598-019-40565-y
|View full text |Cite
|
Sign up to set email alerts
|

Considering tumour volume for motion corrected DWI of colorectal liver metastases increases sensitivity of ADC to detect treatment-induced changes

Abstract: ADC is a potential post treatment imaging biomarker in colorectal liver metastasis however measurements are affected by respiratory motion. This is compounded by increased statistical uncertainty in ADC measurement with decreasing tumour volume. In this prospective study we applied a retrospective motion correction method to improve the image quality of 15 tumour data sets from 11 patients. We compared repeatability of ADC measurements corrected for motion artefact against non-motion corrected acquisition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The stability and repeatability of ADC measurements in this multicentre setting, which critically affects the performance of a biomarker [2], should have been adequate to test our hypothesis. The baseline reproducibility of ADC metrics on three of the scanners from different vendors in this study investigated in a preliminary study of 20 patients with colorectal liver metastases and imaged using the same protocols as in the current study showed a coefficient of variation (CoV) of 6.2% and 95% limits of agreement of 21% [7]. This is highly comparable with the results from other single centre studies; the CoV of ADC measurements in abdominal organs in single centre studies has been shown to vary between 1.7 and 7% [7,23] with 95% limits of agreement ranging from approximately 10-30%.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The stability and repeatability of ADC measurements in this multicentre setting, which critically affects the performance of a biomarker [2], should have been adequate to test our hypothesis. The baseline reproducibility of ADC metrics on three of the scanners from different vendors in this study investigated in a preliminary study of 20 patients with colorectal liver metastases and imaged using the same protocols as in the current study showed a coefficient of variation (CoV) of 6.2% and 95% limits of agreement of 21% [7]. This is highly comparable with the results from other single centre studies; the CoV of ADC measurements in abdominal organs in single centre studies has been shown to vary between 1.7 and 7% [7,23] with 95% limits of agreement ranging from approximately 10-30%.…”
Section: Discussionmentioning
confidence: 67%
“…The baseline reproducibility of ADC metrics on three of the scanners from different vendors in this study investigated in a preliminary study of 20 patients with colorectal liver metastases and imaged using the same protocols as in the current study showed a coefficient of variation (CoV) of 6.2% and 95% limits of agreement of 21% [7]. This is highly comparable with the results from other single centre studies; the CoV of ADC measurements in abdominal organs in single centre studies has been shown to vary between 1.7 and 7% [7,23] with 95% limits of agreement ranging from approximately 10-30%. In comparison, in multicentre studies, ADC measurement variability is greater as a result of differences between imaging platform, manufacturer, scanner model, and field strength [6,24].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Other specific points of attention when calculating ADC include pre-processing of the image data. For example, to minimize the effect of motion, registration between b-values is recommended [ 51 ], and is available on most MRI scanner software, including the Unity MRI-linac. As a minimum, b-value images should visually be inspected for motion and artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was a retrospective study with inherent methodological limitations. For example, due to the lack of raw data, no motion correction of the individual images 43 could be performed before averaging. Second, although the total number of lesions included was relatively large, only common lesion types were analyzed, which may affect the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%